PS-C08-12: SHORT-TERM BLOOD PRESSURE VARIABILITY AND TARGET-ORGAN EFFECTS IN YOUTH: THE SHIP-AHOY STUDY. (January 2023) - Flynn, Joseph; Ferguson, Michael; Lande, Marc; Meyers, Kevin; Samuels, Joshua; Urbina, Elaine
Abstract : Background: Increased blood pressure variability (BPV) has been associated with development of hypertensive target organ damage in adults, including left ventricular (LV) hypertrophy and increased vascular stiffness. Whether similar relationships can be seen in youth is unknown. Methods: We assessed short-term BPV and its relation to LV mass and carotid-femoral pulse wave velocity (cfPWV) in 374 participants (mean age 15.5 years, 60% male) in the SHIP-AHOY cohort. Short-term BPV was assessed by examining the differences in systolic and diastolic blood pressure (S/DBP) between 2 SHIP-AHOY study visits. Average time between visits was 25 days. BP was measured by auscultation; 4 BP measurements were conducted at each visit and averaged. BPV was calculated as the difference between the mean BP measurements at the 2 visits. LV mass was measured by m-mode echocardiography and cfPWV was assessed using plethysmography. Results: Mean SBP was 123.1 ± 13.0 mmHg on day 1, and 122.3 ± 12.8 mmHg on day 2, with a mean difference of 0.9 ± 7.5 mmHg between the visits. Mean DBP was 71.6 ± 11.6 mmHg on day 1, and 72.0 ± 11.7 mmHg on day 2, with a mean difference of 0.5 ± 10.4 mmHg between the visits. Participants were then divided into 2 groups according to whether their BPV was above (n = 198) or below (n = 176) the median BPV of the entire cohort. LV mass was similar between the groups: 32.7 ± 7.3 gram/ht^2.7 for those above the median vs. 32.8 ± 6.7 for those below the median (P = NS), but cfPWF was significantly higher in those with BPV above the median: 5.2 ± 0.9 meters/second vs. 5.0 ± 0.8 m/s for those below the median, P = 0.03. Conclusions: These data suggest that increased short-term BPV may be associated with the development of increased vascular stiffness in youth.